Sparky! - Offill, Jenny, 1968-; Appelhans, Chris (New York : Schwartz & Wade Books, 2014)
A child takes a sloth named Sparky as a pet.
Keywords: Sloths as pets -- Juvenile fiction; Pets -- Juvenile fiction